The Ethiopian Constitutional Promises to the Nation and Nationalities: The Myth and the Operational Reality - Aytaged, Nigussie Afesha (Bahir Dar University Journal of Law, 2022)
Federalism has been formally ushered into the Ethiopian Constitution. Stemming from the multiethnic nature of the Ethiopian state, the Constitution gives focused attention to the rights of the Nations, Nationalities and Peoples (NNP) and recognition to their involvement in all aspects of the countryâ€™s political life. In doing so, the Constitution has made several promises. These are, inter alia, creating one economic and political community, promoting the NNP culture, exercising full measure of self-governance and having equitable representation in the military. This article examines how these constitutional promises operate in practice and looks into the Ethiopian progress towards fulfilling these constitutional promises. This article also argues that the Ethiopian federal system has come some distance towards building one economic and political community and promoting NNP culture and language. However, there are poor records in realizing NNP who do not have their own regional state and have been subsumed in the nine regional states to establish their own state. There is also an unsatisfactory record with respect to equitable representation of various NNPs in the executive branch and the army. This article puts forward some solutions that would help tackle the aforementioned limitations. Primarily, the government must allow NNPs to exercise the right to unconditional state formation as vividly promised by the constitution. Otherwise, the constitution shall incorporate some conditions like â€œserous causeâ€, the fulfillment of which is required for the exercise of the right to establish oneâ€™s own regional state. As far as equitable representation in the federal and state government institution, including the army, is concerned, there should be a mechanism that ensures fair representation and creates functional societies where all NNP have opportunities to participate in the political administration, army and the executive branch.